Determination of site-site distance and site concentration within polymer beads: A combined swelling-electron paramagnetic resonance study - Marchetto, Reinaldo [UNESP]; Cilli, Eduardo Maffud [UNESP]; Jubilut, G. N.; Schreier, S.; Nakaie, C. R. (Amer Chemical Soc, 2005)
[GRAPHICS]This work proposes a combined swelling-electron paramagnetic resonance (EPR) approach aiming at determining some unusual polymer solvation parameters relevant for chemical processes occurring inside beads. Batches of benzhydrylamine-resin (BHAR), a copolymer of styrene-1% divinylbenzene containing phenylmethylamine groups were, labeled with the paramagnetic amino acid 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amine-4-carboxylic acid (TOAC), and their swelling properties and EPR spectra were examined in DCM and DMF. By taking into account the BHARs labeling degrees, the corresponding swelling values, and some polymer structural characteristics, it was possible to calculate polymer swelling parameters, among them, the volume and the number of sites per bead, site-site distances and site concentration. The latter values ranged from 17 to 170 angstrom and from 0.4 to 550 mM, respectively. EPR spectroscopy was applied to validate the multistep calculation strategy of these swelling parameters. Spin-spin interaction was detected in the labeled resins at site-site distances less than approximately 60 A or probe concentrations higher than approximately 1 x 10(-2) M, in close agreement with the values obtained for the spin probe free in solution. Complementarily, the yield of coupling reactions in different resins indicated that the greater the inter-site distance or the lower the site concentration, the faster the reaction. The results suggested that the model and the experimental measurements developed for the determination of solvation parameters represent a relevant step forward for the deeper understanding and improvement of polymer-related processes.